2022
DOI: 10.1016/j.annonc.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human phase 1 study of the anti-TIGIT antibody vibostolimab as monotherapy or with pembrolizumab for advanced solid tumors, including non-small-cell lung cancer☆

Abstract: Background: In this first-in-human phase 1 study (NCT02964013; MK-7684-001), we investigated the safety and efficacy of the anti-TIGIT (T cell immunoglobulin and ITIM domain) antibody vibostolimab as monotherapy or in combination with pembrolizumab. Patients and methods: Part A enrolled patients with advanced solid tumors, and part B enrolled patients with nonsmall-cell lung cancer (NSCLC). Patients received vibostolimab 2.1-700 mg alone or with pembrolizumab 200 mg in part A and vibostolimab 200 mg alone or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(87 citation statements)
references
References 19 publications
(21 reference statements)
2
74
0
Order By: Relevance
“…Patients with advanced solid tumors who received vibostolimab alone or combined with the anti-PD-1 pembrolizumab in a phase I clinical trial (NCT02964013) showed controllable tolerance across escalating doses and all types of advanced solid tumors assessed. Increased NK cell activation of CD8 + T cells was found to have an anticancer effect in the study ( 180 ).…”
Section: Therapeutic Strategies Targeting Tigit Immune Checkpoint Exp...mentioning
confidence: 85%
“…Patients with advanced solid tumors who received vibostolimab alone or combined with the anti-PD-1 pembrolizumab in a phase I clinical trial (NCT02964013) showed controllable tolerance across escalating doses and all types of advanced solid tumors assessed. Increased NK cell activation of CD8 + T cells was found to have an anticancer effect in the study ( 180 ).…”
Section: Therapeutic Strategies Targeting Tigit Immune Checkpoint Exp...mentioning
confidence: 85%
“…Tumor responses (CR, complete remission; PR, partial response; SD, stable disease; and PD, progressive disease) were assessed by the Response Evaluation Criteria in Solid Tumors (RECIST version 1.1) (43)(44)(45)(46). The disease control rate (DCR) was defined as all positive responders (including complete, partial, and stable responders) divided by the total number of response-evaluable patients.…”
Section: Discussionmentioning
confidence: 99%
“…A confirmatory phase III trial is ongoing in this patient population (ClinicalTrials.gov identifier: NCT04294810). Early results from a phase I trial of another anti-TIGIT antibody vibostolimab has shown clinical activity in combination with pembrolizumab in PD-1/PD-L1 naïve and refractory patients with advanced NSCLC ( 61 ). An ongoing phase III trial is comparing combination of vibostolimab plus pembrolizumab with pembrolizumab alone in patients with PD-L1 positive advanced NSCLC (ClinicalTrials.gov identifier: NCT04738487).…”
Section: Immunotherapy Approaches Beyond Pd-1/pd-l1 and Ctla-4 Inhibi...mentioning
confidence: 99%